Activating mechanism of transcriptor NF-kappaB regulated by hepatitis B virus X protein in hepatocellular carcinoma - Wang, Tao (World J Gastroenterol, 2004)
AIM: To investigate the mechanism and significance of NF-κB activation regulated by hepatitis B virus X protein (HBx) in hepatitis B virus (HBV)-associated hepatocellular carcinoma (HCC). METHODS: The expression levels of HBx, p65, IκB-α and ubiquitin were detected by immunohistochemistry in HCC tissue microarrays (TMA) respectively, and IκB-α was detected by Western blot in HCC and corresponding liver tissues. RESULTS: The percentage of informative TMA samples was 98.8% in 186 cases with a total of 367 samples. Compared with corresponding liver tissues (60.0%), the HBx expression was obviously decreased in HBV-associated HCC (47.9%, u = 2.24, P < 0.05). On the contrary, the expressions of p65 (20.6% vs 45.3%, u = 4.85, P < 0.01) and ubiquitin (8.9% vs 59.0%, u = 9.68, P < 0.01) were notably elevated in HCC. In addition, IκB-α had a tendency to go up. Importantly, positive relativity was observed between HBx and p65 (χ(2) = 10.26, P < 0.01), p65 and IκB-α (χ(2) = 16.86, P < 0.01), IκB-α and ubiquitin (χ(2) = 8.90, P < 0.01) in HCC, respectively. CONCLUSION: Both active and non-active forms of NF-κB are increased in HBV-associated HCC. Variant HBx is the major cause of the enhancement of NF-κB activity. The activation always proceeds in nucleus and the proteasome complexes play an important role in the activation.